Calculation Method of Price Reduction in International Sale of Goods Contracts - Popović, Milica (Glasnik Advokatske komore Vojvodine, 2024)
The buyer’s right to price reduction has originated from Roman law and became widely accepted in legal systems with continental legal tradition. Regarding international sale of goods, Article 50 of the United Nations Convention on Contracts for the International Sale of Goods is of particular importance. This paper will analyze one of disputed questions regarding price reduction, which arises during buyer’s exercise of the right to price reduction. In order to perceive the problem completely, the paper deals with origin, legal sources of price reduction in international sales contracts, its distinction from compensation of damages, as well as legal requirements for its application. The focus of this paper is the question of calculation of price reduction with special reference to the time and place of determining the value of conforming and non-conforming goods for the purpose of comparison and applying calculation formula. These questions were disputed during drafting of the Convention and today they are subject of many discussions in legal theory, while the case law is not harmonized enough. The purpose of this article is to draw conclusion on relevant method for calculation of price reduction through the analysis of the provisions of Convention, legal theory and case law.
Keywords: price reduction; international sale of goods contract; Article 50; The United Nations Convention on Contracts for the International Sale of Goods; calculation method; time of calculation; place of calculation